2011
DOI: 10.1111/j.1467-8535.2009.01012.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the effects of using dynamic geometry software and physical manipulatives on the spatial visualisation skills of pre‐service mathematics teachers

Abstract: The study compared the effects of dynamic geometry software and physical manipulatives on the spatial visualisation skills of first-year pre-service mathematics teachers. A pre-and post-test quasi-experimental design was used. The Purdue Spatial Visualisation Test (PSVT) was used for the pre-and post-test. There were three treatment groups. The first group (n = 34) used Dynamic Geometry Software (DGS) Cabri 3D as a virtual manipulative and the second group (n = 32) used physical manipulatives. In the control g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
0
12

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(75 citation statements)
references
References 22 publications
5
58
0
12
Order By: Relevance
“…The experimental group's opportunity to generate their own feedback on computer screens may have been a major factor in the difference in achievement between the two groups. Baki et al (2011) found that using DGS and generating their own feedback made a crucial contribution to pre-service teachers' cognitive development. A similar contribution to younger learners' cognitive development is an implication of this study.…”
Section: Discussionmentioning
confidence: 99%
“…The experimental group's opportunity to generate their own feedback on computer screens may have been a major factor in the difference in achievement between the two groups. Baki et al (2011) found that using DGS and generating their own feedback made a crucial contribution to pre-service teachers' cognitive development. A similar contribution to younger learners' cognitive development is an implication of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Το ψηφιακό σχολείο αποτελεί μία απόδειξη αυτής της επιταγής. Πλήθος ερευνών αναγνωρίζει την προστιθέμενη αξία της χρήσης των ΝΤ στην εκπαίδευση καθώς και στην Εκπαίδευση από Απόσταση (ΕαΑ) (Baki, Kosa & Guven, 2011;Brecht & Ogilby, 2008;Rovai & Jord, 2004;Taradi, Taradi, Radic & Pokrajac, 2004). Όμως, η προστιθέμενη παιδαγωγική αξία των ΝΤ στη μαθησιακή πράξη εξαρτάται από τον τρόπο με τον οποίο αξιοποιούνται τα τεχνολογικά εργαλεία (Κυνηγός & Δημαράκη, 2002), δηλαδή είναι άρρηκτα συνδεδεμένη με τον εκπαιδευτικό σχεδιασμό αξιοποίησης των εργαλείων αυτών και όχι τόσο από τα ίδια τα τεχνολογικά εργαλεία (Κυνηγός, 2009).…”
Section: εισαγωγήunclassified
“…As described previously, these objects are sometimes real-life objects, such as forks or scissors. In other cases, geometry objects of varying familiarity or complexity are used ( [44,45]). Patel and Brian [46] presented a set of 12 Geons that were based on [47].…”
Section: D Geometry Objectsmentioning
confidence: 99%